PEMANFAATAN POSTER LITERASI DIGITAL BERBASIS CANVA DALAM PEMBELAJARAN BAHASA INDONESIA SISWA KELAS X DI UPT SMKN 1 SINJAI - M. Nur, A. Nurchalifah; Usman; Nurhusna (STKIP Subang, 2026)
The Utilization of Canva-Based Digital Literacy Posters in Indonesian Language Learning for Grade X Students at UPT SMKN 1 Sinjai. This study aims to describe the planning, implementation, and assessment of the use of Canva-based digital literacy posters in Indonesian language learning for tenth-grade students at UPT SMKN 1 Sinjai. The study employs a descriptive qualitative approach, focusing on systematically portraying the process of implementing digital poster media within the learning context. Research data were collected through observation, interviews, and documentation. The findings indicate that during the planning stage, teachers and researchers collaborated in developing teaching modules, selecting literacy themes, and designing digital posters using Canva. During the implementation stage, the posters were used as preliminary reading materials to increase students’ reading interest and to facilitate their understanding of information through concise texts and engaging visuals. In the assessment stage, teachers conducted formative evaluations through oral question-and-answer sessions to measure students’ comprehension, confidence, and active participation in responding to the poster content. Overall, the use of Canva-based digital literacy posters proved effective in enhancing student engagement, strengthening their understanding of texts, and creating a more interactive learning environment. Furthermore, the research findings align with Paul Gilster’s concept of digital literacy, which emphasizes the ability to understand, evaluate, and critically interpret digital information. Therefore, Canva-based digital posters are suitable for use as alternative learning media that are relevant to the characteristics of vocational high school students and the demands of 21st-century literacy.